Pop-up Polanyi: Cultural entrepreneurs and the ‘vacancy fix’ - Scott, Michael; Szili, Gerti (City, Culture and Society, 2017)
Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – ‘pop-up shops’ – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how ‘pop-up’ programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how ‘vacancy fixes’ are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification.
Sociology; Geography
Keywords: creative cities; cultural entrepreneurs; gentrification; modes of economic integration; pop-up; rent gap

'Playing on the break': Karl Polanyi and the double-movement 'Against Modern Football' - Webber, David M (International Review for the Sociology of Sport, 2017)
While the popularity of English football increases worldwide, there has been a marked rise in the discontent expressed by a small but growing group of domestic fans. This dissent has led to the emergence of a movement broadly defined as being 'Against Modern Football' (AMF), a banner under which fans of rival clubs have gathered in an attempt to challenge the poor governance, commercialism and greed that has come to dominate the English game. This article offers a conceptualisation of what it means to be 'against modern football' based upon Karl Polanyi's analysis of the market society. Developing the dialectic of the 'double-movement' that appears in Polanyi's most famous work, The Great Transformation, this article demonstrates how these governing principles might be useful in explaining both the complex cultural political economy of English football and the possibilities that exist for the AMF movement to socially re-embed the modern game.
Sociology
Keywords: English football; athletic clubs; cultural political economy; soccer; sociology of sport; sports - social aspects; sports spectators; supporters

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
History; Sociology
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Karl Polanyi in an Age of Uncertainty - Block, Fred; Somers, Margaret R. (Contemporary Sociology, 2017)
Sociology
Keywords: DALE; Gareth; For a New West: Essays 1919-1958 (Book); Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; book review; nonfiction; socialism

Innovazione sociale e città - Vicari, Serena; Mingione, Enzo (SOCIOLOGIA URBANA E RURALE, 2017)
L’articolo discute di innovazione sociale sulla base dell’analisi di Polany e di Marshall e dei contributi successivi che si sono sviluppati a partire da quel quadro teorico. Le ragioni dell’innovazione sociale vengono interpretate alla luce della crisi del welfare capitalism e dei disequilibri che si sono manifestati nelle istituzioni fonti di integrazione e coesione sociale. Gli autori propongono una valutazione dei processi e delle esperienze di innovazione sociale che ne mette in luce la rilevanza, ma anche l’ambivalenza e i limiti nel rispondere alla crisi. This article discusses the concept of social innovation on the basis of Polany’s and Marshall’s analyses and of more recent contributions working within that theoretical framework. The authors propose an interpretation of social innovation on the basis of the crisis of welfare capitalism and of the instability of the institutional foundations of social cohesion and integration. The relevance but also the ambivalence and limits of the processes and practices of social innovation are discussed and evaluated as potential responses to this crisis.
Sociology
Keywords: social innovation

Free market ideology and deregulation in Colorado’s oil fields: Evidence for triple movement activism? - Malin, Stephanie A.; Mayer, Adam; Shreeve, Kelly; Olson-Hazboun, Shawn K.; Adgate, John (Environmental Politics, 2017)
Unconventional oil and gas extraction (UOGE) has spurred an unprecedented boom in onshore production in the US. Despite a surge in related research, a void exists regarding inquiries into policy outcomes and perceptions. To address this, support for federal regulatory exemptions for UOGE is examined using survey data collected in 2015 from two Northern Colorado communities. Current regulatory exemptions for UOGE can be understood as components of broader societal processes of neoliberalization. Free market ideology increases public support for federal regulatory exemptions for UOGE. Perceived negative impacts do not necessarily drive people to support increased federal regulation. Utilizing neo-Polanyian theory, interaction between free market ideology and perceived negative impacts is explored. Free market ideology appears to moderate people’s views of regulation:increasingthe effect of perceived negative impacts while simultaneously increasing support forderegulation. To conclude, the ways in which free market ideology might normalize the impacts of UOGE activity are discussed.
Sociology
Keywords: Colorado; deregulation - government policy; double movement; environmental sociology; fracking; free enterprise; free markets; gas extraction; hydraulic fracturing; market ideology; neoliberalism; oil fields; public support; triple movement; unconventional oil and gas production

Fixing network failures? The contested case of the American Manufacturing Extension Partnership - Brandt, Philipp; Whitford, Josh (Socio-Economic Review, 2017)
The article uses a case study of the American Manufacturing Extension Partnership to explore economic and industrial policy in the contemporary USA. Extensive quantitative and qualitative data are mobilized to show that: (a) the agency is pressured politically to limit its activities to 'blunt' remedies for identifiable 'market failures'; even as (b) regional centers in fact often orient also, and sometimes instead, toward 'coordination-oriented' policies to mitigate 'network failures'; and (c) these latter generate better results, on average, for client manufacturers. The findings challenge neo-institutional claims that economic policies are most effective only when complementary to the dominant institutional coordinating capacities embedded in the existing American political economy, or when they have the exceptional support of the American security establishment. They are, however, consistent with an alternative neo-Polanyian approach that explains when and how streetlevel policymakers dispersed across American federalism sometimes sidestep the ideological hegemony of 'market fundamentalism'.
Sociology
Keywords: United States; economic policy; embeddedness; industrial organization; industrial policy; institutional complementarity; manufactures; market failure; market fundamentalism; partnership (business); public policy; regional economies

The four modes of coexistence in social systems - Nechansky, Helmut (Kybernetes, 2017)
Purpose The paper aims to relate the four modes of coexistence of goal-orientated systems – conflict, hierarchy, the niche and cooperation – to static behavioral descriptions of social systems.Design/methodology/approach Analyzing the options for interactions of goal-orientated systems leads the four modes of coexistence. These show certain behavioral characteristics. Searching for these characteristics in selected behavioral descriptions in organizational theory, sociology, political science and system science allows relating them to certain modes.Findings In organizations, the four modes of coexistence show in general (Cameron and Quinn) and dyadic interaction patterns (Argyris). In sociology, they show in educational schemes preparing for specific modes (Bernstein) and in different exchange patterns (Polanyi). In political theory, the four modes of coexistence show in preferred policies of parties, in institutional development, in oligarch power politics (Winters) and in external policy. In system science, they show in problem solving strategies (Jackson) and “mindscapes” (Murayama).Research limitations/implications The analysis is restricted to static patterns leaving out dynamic developments, for example, in networks.Practical implications Together with previous investigations, the paper shows how behavioral descriptions ranging from psychology to politics correspond to the four modes of coexistence, and it suggests interrelations and alignments of the modes via various levels of societal organization.Originality/value The four modes of coexistence provide an unequivocal theoretical framework that allows finding parallels in behavioral descriptions ranging from psychology via sociology to politics.
Sociology
Keywords: business planning; cybernetics; decision making; decision-making; forms of integration; industrial organization (economic theory); interaction; politics; redistribution; sociology; systems theory

‘Hipster Capitalism’ in the Age of Austerity? Polanyi Meets Bourdieu’s New Petite Bourgeoisie - Scott, Michael (Cultural Sociology, 2017)
This article dialogues Polanyi and Bourdieu to propose a new research agenda within the sociology of cultural production. Extending recent literature on hipsters, this iconic figure is shifted from the world of consumption to the world of production via Bourdieu’s conceptualisation of the new petite bourgeoisie. Using secondary empirical material of cultural micro-enterprises, two ideal-typical career strategies are sketched: cultural-capital oriented seeking to secure positions within established creative industries, and economic-capital orientated stylising ‘old’ petite bourgeoisie occupations to access economic returns. However, within the context of ongoing austerity policies, Bourdieu’s economic capital does not fully account for the variegated forms of material resources these nascent enterprises draw on. Bringing Polanyi’s modes of economic integration – reciprocity, redistribution and exchange – to Bourdieu opens new questions on how hipster capitalism is the practice of intermediating between these ‘backstage’ material modes and the ‘frontstage’ selling of style.
Sociology
Keywords: BOURDIEU; Pierre; 1930-2002; austerity; capitalism; cultural capital; cultural production; cultural sociology; hipster; hipsters (subculture); micro-enterprise; modes of economic integration; new cultural economy; new petite bourgeoisie

Karl Polanyi on the Rise of Fascism and Market Economy - Komlik, Oleg (Economic Sociology and Political Economy, 2017)
A spectre is haunting Europe and the world — the spectre of Fascism (veiled as defensive democracy and common-sense patriotism) and authoritarian neoliberalism (disguised as social protectionism an…
Sociology
Keywords: economic sociology; fascism

The State in Classical Laissez-Faire, Its Crisis, and the Establishment of Fordism - Bonanno, Alessandro (The Legitimation Crisis of Neoliberalism, 2017)
This chapter stresses the point that contrary to arguments proposed by neoliberals, the state has consistently been a relevant actor in the organization of the economy and society. It indicates that the role played by the state was fundamental in the expansion and stability of capitalism in its early stages, during the laissez-faire era of the nineteenth century and under Fordism in the twentieth century. This argument is illustrated through a review of salient aspects of classical liberal theories of the state such as those of John Locke, Adam Smith, Jeremy Bentham, and John Stuart Mill and a brief review of the theory of Marx and early twentieth century contributions such as those of Karl Polanyic and John M. Keynes. An analysis of the theories of the role of the state under Fordism is proposed in the final sections of the chapter.
Sociology
Keywords: Fordism; MARX; Karl; 1818-1883; double movement; economic sociology; organizational studies; regulated capitalism

Deindustrialisation and the Historical Sociological Imagination: Making Sense of Work and Industrial Change - Strangleman, Tim (SOCIOLOGY-THE JOURNAL OF THE BRITISH SOCIOLOGICAL ASSOCIATION, 2017)
Following recent calls for a more self-aware and historically sensitive sociology this article reflects on the concept of deindustrialisation and industrial change in this spirit. Using EP Thompson’s classic The Making of the English Working Class and his examination of industrialising culture with its stress on experience, the article asks how these insights might be of value in understanding contemporary processes of deindustrialisation and work. Drawing on a range of sociological, cultural and literary studies it conceptualises the differences and similarities between two historic moments of industrial change and loss. In particular it draws on the literary concept of the ‘half-life of deindustrialisation’ to explore these periods. The article has important implications for how we think about contemporary and historical industrial decline.
Sociology
Keywords: THOMPSON; E. P. (Edward Palmer); 1924-1993; half-life of deindistrialisation; historical sociology; work meaning and identity